Penentuan kapasiti dan jenis pencerapan zeolit asli terhadap bahan pencelup sintetik - Mee, Kin Chai; Hussain, Asiah; Ramli, Zainab (Malaysian Society of Analytical Sciences, 2001)
Zeolite, which is recognised as a molecular sieve, has fine pore size and high surface area has been used as an adsorbent to adsorb synthetic basic dye from coloured wastewater. Natural mordenite zeolite originated from Indonesia was modified to its base form and its adsorption capacity towards synthetic basic yellow 11 was determined. The type of adsorption of the zeolite sample towards synthetic basic dye was determine by four methods, name by the affect of calcination of zeolite sample on the adsorption capacity, regeneration of the zeolite sample, determination of the changes of structural characteristics and determination of the changes of cation property. This study shows that the zeolite sample has very high adsorption capacity toward synthetic base dye. Calcination of the zeolite sample and thermal regeneration result in a decreased of the adsorption capacity. The unchanged of structural characteristics and natrium ion exchange in zeolite sample after adsorption and regeneration indicate that the type of adsorption in the adsorption process of zeolite sample towards synthetic dye were a mixture of chemisorption and physisorption.